Endoscopic combined intrarenal surgery versus percutaneuos nephrolithotomy for complex pediatric stone disease: A comparative analysis of efficacy and safety. - ŞEKERCİ, ÇAĞRI AKIN (My University, 2024)
Introduction Decision-making for complex pediatric urinary system stone disease is still a challenge for pediatric urologists. The interest in supine percutaneous nephrolithotomy (PCNL) is increasing among centers to achieve high surgical success rates with less morbidity. Despite advanced retrograde intrarenal surgery armamentarium, percutaneous approaches remain the first-line surgical treatment modality for >2 cm and complex renal stones. There are no comparative studies yet in the literature for pediatric endoscopic combined intrarenal surgery (ECIRS) Objective In this study, we aimed to contribute to the literature by evaluating the safety and efficacy of ECIRS by comparing it with PCNL. Study design Patients under 18 years of age who underwent PCNL and ECIRS for urinary tract stone disease at our Pediatric Urology department between 2012 and 2024 were included. Preoperative (demographic characteristics, stone characteristics, biochemical parameters), perioperative (duration of surgery, number of accesses, lasing and fluoroscopy times, endoscopic and fluoroscopic stone-free rates) and postoperative (hospital stay, urinary tract infection, complication and radiological stone-free rates) parameters were retrospectively evaluated. Results A total of 68 children [28 (41%) girls and 40 (59%) boys] aged 5 (0e17) years were included in the study. ECIRS was performed in 19 (28%), supine in 28 (41%) and prone PCNL in 21 (30%) patients. Age (p Z 0.029), Guy’s stone score (p < 0.001), S.T.O.N.E. (p < 0.001), and Seoul National University Renal Stone Complexity (S-ReSC) scores (p Z 0.001) for preoperative parameters were found to be higher in ECIRS group over both PCNL methods (Summary Table). However, Clinical Research Office of the Endourological Society (CROES) score was seen lower for ECIRS group patients compared to other groups (p Z 0.028). Surgery time (in favor of supine over prone PCNL), fluoroscopy time (in favor of ECIRS and Supine PCNL over Prone PCNL), preferred laser type (prone PCNL group was mostly performed with holmium laser, whereas other groups were balanced between Holmium and Thulium Fiber Laser) and exit strategy (the preferred exit strategy was DJ Stent in most of the ECIRS patients, whereas nephrostomy tube was used in some of the PCNL group) showed significant difference among the groups as perioperative parameters (p Z 0.042, <0.001, <0.001, <0.001, respectively). Surgery time was lower for supine PCNL compared to prone PCNL. For postoperative parameters, stone-free rates, complication rates and urinary tract infections were similar between the 3 groups, while a difference was detected in terms of length of hospital stay in favor of ECIRS over both supine and prone PCNL (p Z 0.006). Discussion The current trial suggests that stone-free and complication rates of ECIRS and supine PCNL were similar in the pediatric complex stone patients. Although, the stones in the ECIRS group we found to be more complex. Also, ECIRS was superior to PCNL in terms of fluoroscopy exposure and hospital stay. Conclusion With the widespread use of new generation ureteral access sheaths and flexible ureterorenoscopes, ECIRS may have an important role in treatment of complex pediatric kidney stones.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Pediatrik Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Pediatric Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology; Children; Kidney stone; PCNL; ECIRS; Stone free rate; Complication